Fenomena Kekentalan Fluida Minyak Kelapa Sawit Terhadap Kemampuan Pompa Sentrifugal Pada Unit Vacuum Dyer - Golfrid Gultom; M Dimas Gunawan (JURNAL VOKASI TEKNIK, 2023)
Increasing the productivity of a vacuum dryer as a water separator with oil is needed by fluid machines such as pumps. The centrifugal pump functions to pump palm oil fluid from the clean oil tank to the vacuum dryer with a capacity of 10 tons/hour. The problem found in the pump is the viscosity or thickness of the flowing fluid. This study aims to determine the phenomenon or influence of fluid viscosity on the performance of centrifugal pumps. Variations were made at a temperature of 85oC with a viscosity of 10.43 cSt, a temperature of 90oC with a viscosity of 9.45 cSt, and a temperature of 95oC with a viscosity of 8.61 cSt. Based on the results of testing and analysis, it is stated that the greater the value of the fluid viscosity, the greater the power value of the pump shaft. As the fluid temperature increases, the viscosity value of the fluid will decrease. This will reduce the working load of the pump shaft so that the rotation of the turbine is higher, the more fluid flow to be pumped and the value of the pump head will increase.